Pengembangan Aplikasi Kasir Berbasis Android pada Usaha Kecil Menengah (UMKM) - Cindy Cahyaning Astuti; Akbar Wiguna; Aprillia Bellanda Firmansyah; Muhammad Aziz Rohmatulloh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Abstr This community service project aims to develop and implement an Android-based point-of-sale application at Kedai Sasya to address efficiency issues caused by the continued use of manual transaction and inventory tracking systems. The project was carried out using the Participatory Action Research (PAR) method, which actively involves partners throughout the stages of planning, action, observation, and participatory reflection. Technically, during the action phase, the application was developed using the Waterfall software development approach, which includes requirements analysis, design, implementation, and testing. The resulting application is equipped with features for digital transaction recording, menu management, inventory monitoring, and automated reporting based on Firebase. Based on the results of testing and participatory evaluation with users, the implementation of this system has proven successful in accelerating daily transaction processes and significantly minimizing recording errors (human error). Although deemed very helpful, the reflection results indicate the need for further development of real-time stock notification features and the ability to export reports to Excel format. Overall, the use of this POS application has successfully improved operational efficiency and supported better business decision-making at Kedai Sasya.